The Urgent Problems in the Sphere of Student's Mental Health: Challenge of COVID-19 Pandemic - O. V. Volkova (Kemerovo State University, 2021)
The research featured the urgent issues of students’ mental health triggered by the COVID-19 pandemic. The pandemic has become frustrating and degrading in relation to a number of needs that young people regard as significant. It violated the usual behavioral patterns of self-actualization and self-realization. The lockdown and distance learning put an unexpected burden on the personal and health resources of students, leading to the risk of hypochondrial response and triggering various forms of maladaptive and addictive behavior. These violations worsened the emotional background, affected the motivational sphere,   and limited the ability of self-control and self-organization, thus  creating prerequisites for learned helplessness and addictive behavior, which are one of the most destructive responses to stress. The authors believe that students need a special program of psychological support aimed at solving the mental health issues caused by the COVID-19 pandemic.